Experimental testing of a masonry arch bridge model subject to increasing level of damage - Degiovanni, L.; Quattrone, Antonino; Zanotti Fragonara, Luca; Ceravolo, Rosario; De Stefano, Alessandro (European Commission, 2011)
Masonry arch bridges are particularly sensitive to the bearings loss produced by scour of the streambed soil at the piers foundations. A 1:2 scaled experimental model of a masonry arch bridge was built to study the evolution of the damage mechanism related to the application of foundation movements. The model was built with handmade clay bricks and a mortar with poor mechanical properties in order to reproduce typical materials of historical constructions, and an extensive characterization of the materials has been carried out. The mid-span pier is placed on a settlement application system, expressly designed to simulate the scour effect, quantified through hydraulic flume tests performed on a further scaled down model. Damage levels of increasing intensity have been simulated through the application of pier settlements and rotations. Experimental vibration tests were performed on the undamaged structure and after each settlement step. Both the environmental noise and the impacts of a sledge hammer were used as excitation sources. A complete dynamic identification was carried out and the variation of modal parameters at different levels of damage monitored. Moreover, the use of a testing shaker allowed investigating the non - linear behaviour of the damaged model.
Keywords: Masonry Arch Bridge; Structural Health Monitoring; Operational Modal Analysis